Synthesis, Characterization and Study of the Biological Activity of New Metal Complexes of Ligand[2-(3-benzoylthioureido)-3-(-4-hydroxyphenyl) Propanoic Acid (BHP) - Enass Jasim Waheed (Journal of Global Pharma Technology, 2016)
In this paper, series of new complexes of Manganese(II), Cobalt(II), Nickel (II) Cupper(II) Zinc(II), Cadmium(II) and Mercury (II) are prepared from the new ligand  [2-(3-benzoylthioureido)-3-(-4-hydroxyphenyl) propanoic acid (BHP) derived from tyrosine and benzoylisothiocyanate .Chemical structures are obtained from their 1 H, 13CNMR spectra (for BHP), elemental microanalyses, molar conductance, FTIR, UV–Vis, magnetic susceptibility in addition to TGA/DTG and DSC analysis, the suggested geometry for all complexes was tetrahedral. The biological activity of BHP and its complexes has been extensively studied against two bacterial species Staphylococcus aurous (G+) and Escherichia coli (G-) by agar-well diffusion technique, where Mn(II), Co(II), Ni (II)  complexes showed greater biological activity compared to ligand. Keywords: Tyrosine, Metal complexes, Biological activity.